2022
DOI: 10.4062/biomolther.2021.136
|View full text |Cite
|
Sign up to set email alerts
|

Betulin Targets Lipin1/2-Meidated P2X7 Receptor as a Therapeutic Approach to Attenuate Lipid Accumulation and Metaflammation

Abstract: The present study focused on the potential mechanism of betulin (BT), a pentacyclic triterpenoid isolated from the bark of white birch ( Betula pubescens ), against chronic alcohol-induced lipid accumulation and metaflammation. AML-12 and RAW 264.7 cells were administered ethanol (EtOH), lipopolysaccharide (LPS) or BT. Male C57BL/6 mice were fed Lieber-DeCarli liquid diets containing 5% EtOH for 4 weeks, followed by single EtOH gavage on the last day and simultaneous treatment with BT (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Earlier research conducted to investigate the effects of betulin on inflammatory damage induced by S. aureus-mastitis in female BALB/c mice showed that betulin ameliorated histopathological changes and suppressed the expression of IL-1β, TNF-α, and IL-6 initiated by the inflammatory injury, acting as a protective anti-inflammatory agent against mastitis [97]. Additionally, betulin prevented AML-12 or RAW 264.7 cells' activation of P2X7r-NLRP3 in response to EtOH-or lipopolysaccharide-induced inflammation [94]. Sepsis is a complex disease that is established in various modes, including lymphangitis, encephalopathy, renal failure, heart failure, and liver injury, all of which arise from an inflammatory response [5].…”
Section: Preclinical Evidencementioning
confidence: 97%
See 2 more Smart Citations
“…Earlier research conducted to investigate the effects of betulin on inflammatory damage induced by S. aureus-mastitis in female BALB/c mice showed that betulin ameliorated histopathological changes and suppressed the expression of IL-1β, TNF-α, and IL-6 initiated by the inflammatory injury, acting as a protective anti-inflammatory agent against mastitis [97]. Additionally, betulin prevented AML-12 or RAW 264.7 cells' activation of P2X7r-NLRP3 in response to EtOH-or lipopolysaccharide-induced inflammation [94]. Sepsis is a complex disease that is established in various modes, including lymphangitis, encephalopathy, renal failure, heart failure, and liver injury, all of which arise from an inflammatory response [5].…”
Section: Preclinical Evidencementioning
confidence: 97%
“…Elsewhere, betulin, betulinic acid, and oleanolic acid (1 µM each) were investigated for their hepatoprotective activity against ethanol-induced cytotoxicity in HepG2 cells, with betulin being the most active protectant of HepG2 cells against ethanol-induced cytotoxicity [92]. Another study proposed that betulin limited fibrosis formation and attenuated cisplatin-stimulated hepatic damage in rats by targeting apoptosis and NEK7-independent NLRP3 inflammasome pathways [93,94]. In addition, betulin mitigated increased levels of inflammatory factors, including IL-1α, IL-1β, IL-6, IL-18, TNF-α, TGF-β, and MMP2 in ethanol-induced liver stellate cells and chronic EtOHtreated rodents [87,88,94,95].…”
Section: Protective Effects Of Betulin On Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Human LIPIN1 is the ortholog to PAH1 in yeast. It acts as a PA phosphatase and is also one of the critical regulators of cellular lipid metabolism in nuclear membrane biogenesis and various tissues [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Polymorphism in LIPIN isoforms may lead to a poor condition.…”
Section: Ctdnep1 In Nuclear Membrane Biogenesismentioning
confidence: 99%
“…Betulin, a naturally occurring pentacyclic triterpenoid, is mainly isolated from the bark of Betula pubescens, which has a variety of pharmacological effects, including antimalarial, anti-inflammatory, anticancer, and other activities (Alakurtti et al, 2006;Tuli et al, 2021). Betulin significantly alleviated histopathological changes, reduced serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST), triglyceride (TG) levels, and inhibited the secretion of inflammatory factors and blocked the P2X7R-NLRP3 signaling pathway (Dou et al, 2022).…”
Section: Betulinmentioning
confidence: 99%